2013
DOI: 10.3892/or.2013.2672
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of target proteins following Drosha knockdown in cervical cancer

Abstract: Abstract. The nuclear microRNA (miRNA) processing enzyme Drosha is upregulated in cervical cancer, and its overexpression is related to an invasive tumour phenotype. However, the mechanisms that underlie this effect remain poorly understood. The aim of this study was to identify the potential targets of Drosha in cervical cancer. Here, we demonstrated that Drosha knockdown (Drosha-KD) inhibited proliferation, colony formation and the migration of cervical cancer cells in vitro. A global upregulation of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(23 reference statements)
3
3
0
Order By: Relevance
“…1B). In summary, our data are partially consistent with a previous report (Zhou et al, 2013), and show that DROSHA mRNA levels are significantly increased in all HPV positive cervical cancer lines, whereas DICER mRNA levels were only significantly increased in the HPV16 positive CaSki and SiHa but not in the HPV18 positive HeLa or the HPV negative C33A cervical carcinoma lines.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1B). In summary, our data are partially consistent with a previous report (Zhou et al, 2013), and show that DROSHA mRNA levels are significantly increased in all HPV positive cervical cancer lines, whereas DICER mRNA levels were only significantly increased in the HPV16 positive CaSki and SiHa but not in the HPV18 positive HeLa or the HPV negative C33A cervical carcinoma lines.…”
Section: Resultssupporting
confidence: 93%
“…1A). These results partially confirm and extend a previous report that documented increased DROSHA mRNA expression in HeLa, SiHa and C33A cervical cancer cell lines (Zhou et al, 2013). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, in accordance with our results, Li et al reported that GAPDH was significantly increased in malignant ovarian tissues. The altered expression of GAPDH was also found in other types of neoplasia, such as human glioma, atopic bronchial epithelial cells, and squamous cervical cancer [22] [24] .…”
Section: Discussionmentioning
confidence: 74%